Orangia highways (A) - Es?, P?ter; Klibanoff, Peter; Schmedders, Karl; Hunter, Graeme, Dr. (London : Kellogg School of Management, 2006)
In part A of this case, highway procurement auctions are analyzed from the perspective of the buyer-auctioneer. The case provides the results of a regression in which the ratio of the project's price to its estimated cost is regressed on a number of project attributes (including estimated costs, duration, and number of bidders). Students are asked to establish basic facts regarding this estimated relationship (significance of variables, confidence intervals for changes, etc.) and set up and estimate a regression model to predict the winning bid based on project attributes, and compute the probability that the actual winning price will be below the estimated cost.
Originally published in Es?, P., Klibanoff, P., Schmedders, K., & Hunter, G. (2006). Orangia highways (A). 5-106-007(A). Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Road construction contracts -- Case studies; Roads -- Design and construction -- Case studies